1975
DOI: 10.1139/y75-154
|View full text |Cite
|
Sign up to set email alerts
|

The Action of the Ionophores, X-537A and A-23187, on Smooth Muscle

Abstract: The cation ionophore X-537A in the concentration range of 10(-6) to 3 X 10(-5) M produced contractions in the rat and guinea-pig vas deferens. No contractile effect was produced in either of the vasa deferentia preparations by the ionophore A-23187 in the concentration range of 10(-7) to 5 X 10(-5) M. In contrast, X-537A had no contractile effect on the guinea-pig ileal longitudinal smooth muscle while A-23187 produced a dose and [Ca2+] dependent contraction. The contractile effect of X-537A in the vasa defere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

1978
1978
1994
1994

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…Swamy et al (1975) have also reported that X537A inhibits contractile responses to agonists in the intestine.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Swamy et al (1975) have also reported that X537A inhibits contractile responses to agonists in the intestine.…”
Section: Discussionmentioning
confidence: 91%
“…In the vas deferens, unlike A23187, X537A released catecholamine in the absence of calcium (Thoa, Costa, Moss & Kopin, 1974;Ito, Nakazato & Ohga, 1978). Swamy et al (1975) further reported that X537A did not produce a contraction but inhibited the contractile response to muscarinic agonists in the guinea-pig ileal longitudinal smooth muscle. The inhibitory action of X537A on contractile responses to potassium was also observed in vascular smooth muscles (Watson, 1978;Bukoski, Seidel & Allen, 1979;Berner, Disalvo & Schwartz, 1980).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…A23187 produces a contraction which is dependent on the external Ca2+ in smooth muscles (Ishida & Shibata, 1980) by increasing the permeability of the membrane to Ca2+ (Swamy et al, 1975). However, the contraction induced by A23187 was insensitive to verapamil and mexiletine did not induce relaxations in arteries contracted with A23187, indicating that mexiletine does not nonspecifically inhibit contractions which depend on extracellular Ca2+.…”
Section: Discussionmentioning
confidence: 95%